The Effect of the CIRC Model on Reading, Writing, and Numeracy Skills in Second-Grade Elementary School Students - Intan Kusuma Arofati Muntaha; Sri Utaminingsih; Ahmad Bakhruddin (EduBasic Journal: Jurnal Pendidikan Dasar, 2022)
This research was motivated by the low ability to read, write, and count in second-grade elementary school students. This study, therefore, aims to determine the mean difference and improvement in implementing the smartboard-assisted CIRC model to the reading, writing, and numeracy skills of second-grade elementary school students. This study used quantitative research methods with a pre-experimental one-group-pretest-posttest research design. The sample involved was 17 students, with a total sampling technique or census. Data collection techniques were in the form of tests, interviews, observation, and documentation. The results showcased the difference in the mean pretest-posttest scores on the paired sample t-test calculation, indicating that the sig. (2-tailed) = 0.000 0.05, with criteria sig. p 0.05, so H0 was rejected, and Ha was accepted. It can be concluded that there was a difference in the mean pretest-posttest scores of students. Meanwhile, the application of the smartboard-assisted CIRC model in the N-gain test calculation was known to have increased by 0.61, with moderate criteria. From the study results, it can be concluded that there was an increase in students' reading, writing, and numeracy skills through the CIRC model assisted by smartboard media. These results indicate that the smart board-assisted CIRC model can be used as an alternative pair of innovative learning model and media to address learning problems of elementary school students.